Young Males’ Implicit Theories of Marital Relationships: A Thematic Analysis of Socialization Influences - Gaiduk, Julija; Gogoi, Jurgita (Psichologija, 2025)
This study aimed to explore how young males formed implicit theories of a happy marital relationship and identify key socialization influences. Thirteen young adult males studying at a university in Eastern Europe participated in a qualitative study. Semi-structured interviews were conducted online or face-to-face asking the participants to describe their ideas about marriage and what influenced them. The interviews were transcribed and analyzed by using the thematic analysis method. The following key socialization influences on the formation of their ideas about marital relationships have been identified: observations of parental and other relationships, culture (own culture and the culture of others), personal characteristics of the participants, and parenting practices of their parents.